Marginal Integrity of Cervical Restorations with Caries-Affected Dentinal Walls: Effect of Contamination with Hemostatic Agents - Maryam Khoroushi; Fatemeh Keshani; Moeen Hosseini Shirazi; Mehdi Esmaeili (Tehran University of Medical Sciences, 2018)
Objectives: The aim of this study was to compare the microleakage in normal and caries-affected dentin (CAD) and to investigate the effect of three hemostatic agents on the microleakage of Class V composite resin restorations in CAD. Materials and Methods: Ninety-six Class V non-beveled cavities were prepared in 48 third molars at 1 mm below the cementoenamel junction (CEJ) in the cervical margin with the occlusogingival size of 2 mm, mesiodistal dimension of 3 mm, and a depth of 1.5 mm. Next, the teeth were divided into 8 groups (n=12): G1-4 included normal dentin (N) substrate, while G5-8 were exposed to mineralization/demineralization cycles to produce CAD substrate. Groups 1 and 5 were the controls. ViscoStat was used in groups 2 and 6, ViscoStat Clear was used in groups 3 and 7, while trichloroacetic acid (TCA) was used in groups 4 and 8. The cavities were restored with composite resin. The samples were sectioned after thermocycling and immersion in 2% fuchsin for 24 hours. The degree of dye penetration was evaluated under a stereomicroscope at 40× magnification. Data were evaluated using Kruskal-Wallis and Mann-U-Whitney tests in SPSS 15 software (α=0.05). Results: Significant differences were recorded on the mean microleakage of different groups (P=0.047). There was a significant difference in the mean dentinal microleakage between N and CAD groups (P=0.014). The dentinal microleakage in group 3 was significantly higher than that in groups 4 to 8. Conclusions: According to the results, CAD showed less microleakage in comparison with intact dentin. ViscoStat Clear caused a greater microleakage than did ViscoStat or TCA.